Coastal protection and conservation on sandy beaches and dunes: context‐dependent tradeoffs in ecosystem service supply. Issue 4 (21st April 2017) - Biel, Reuben G.; Hacker, Sally D.; Ruggiero, Peter; Cohn, Nicholas; Seabloom, Eric W.
Abstract: Managing multiple ecosystem services (ESs) across landscapes presents a central challenge for ecosystem‐based management, because services often exhibit spatiotemporal variation and weak associations with co‐occurring ESs. Further focus on the mechanistic relationships among ESs and their underlying biophysical processes provides greater insight into the causes of variation and covariation among ESs, thus serving as a guide to enhance their supply while preventing adverse outcomes. Here, we used the U.S. Pacific Northwest coastal dune ecosystem to examine how invasive beachgrass management affects three ESs: coastal protection, western snowy plover conservation, and endemic foredune plant conservation. At seven coastal dune habitat restoration areas, we observed spatial variation in the supply of each ES and further identified a tradeoff between western snowy plover conservation and coastal protection. While the ESs were collectively influenced by the invasive beachgrasses and the foredunes they create, the magnitude of the synergies and tradeoffs were influenced by numerous non‐shared drivers, including nearshore geomorphology, changes in foredune shape as a result of restoration, and other management actions irrespective of restoration. Incorporation of these shared and non‐shared drivers into future coastal management planning may reduce tradeoffs among Pacific Northwest dune ESs. With better understanding of ES relationships, it becomes possible to identify management actions that may enhance synergies and mitigate tradeoffs, leading to better decisions for nature and people.